Compositional schedulability analysis of real-time systems using time Petri nets. - Dianxiang Xu (IEEE Transactions on software engineering)
This paper presents an approach to the schedulability analysis of real-time systems modeled in time Petri nets by separating timing properties from other behavioral properties. The analysis of behavioral properties is conducted based on the reachability graph of the underlying Petri net, whereas timing constraints are checked in terms of absolute and relative firing domains. If a specific task execution is schedulable, we calculate the time span of the task execution, and pinpoint nonschedulable transitions to help adjust timing constraints. A technique for compositional timing analysis is also proposed to deal with complex task sequences, which not only improves efficiency but also facilitates the discussion of the reachability issue with regard to schedulability. We identified a class of well-structured time Petri nets such that their reachability can be easily analyzed.